Feeling jealous - Holmes, Kirsty (New York, NY KidHaven Publishing, an imprint of Greenhaven Publishing, 2019)
Learn about feeling jealous and how to handle it in a healthy way. Nonfiction picture book featuring the character Green-eyed Bunny explains characteristics of embarrassment and how it affects people
Education
1 2 13
Keywords: Jealousy -- Juvenile literature; Jealousy in children -- Juvenile literature